Long-term effects of stump harvesting and landscape composition on beetle assemblages in the hemiboreal forest of Sweden - Andersson, Jon; Hjältén, Joakim; Dynesius, Mats (Forest ecology and management, 2012)
► We investigated the effects from stump harvesting on saproxylic beetles. ► We also studied the effects from forest characteristics on saproxylic beetles. ► The effects from stump harvesting on saproxylic beetles were small. ► The influence on beetle abundances from the surrounding forest was important. Studies on the effects of stump harvesting on forest biodiversity are scarce and studies on long-term effects are until now non-existent. We evaluated such long-term effects by sampling beetles at 14 clear-cuts with and 14 clear-cuts without stump harvesting; harvesting had been done 21–28years before this study. By using window traps, we collected 6429 individuals belonging to 432 species in 55 taxonomic families. To control for potentially confounding effects of among-site variations in landscape setting we also assessed forest age and volume of deciduous trees within the forest surrounding each site. The long-term effects from harvesting on beetle abundance, species richness and species composition was generally small in comparison to the influence of the characteristics of the surrounding forests. The species richness of the beetle family Latridiidae and the functional group fungivores appeared, however, to be negatively affected by the previous stump harvesting, while several other groups showed strong associations to the characteristics of the surrounding forest. We found little support for considerable long-term effects of stump harvesting on beetles flying in the stands. Long-term effects of stump harvesting at the landscape scale accumulated from harvest of many localities may still be severe, and should be the subject of future studies.